2017
DOI: 10.1016/j.anbehav.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Habitat preferences by individual humpback whale mothers in the Hawaiian breeding grounds vary with the age and size of their calves

Abstract: We investigated whether calf age and calf size influence habitat choice by humpback whale mother-calf pairs in their breeding grounds. During 1997-2008, we conducted focal follows of mother-calf pairs in Hawaiian waters. Tail-fluke identification photographs and calf lengths (measured through videogrammetry) were obtained. Water depth and sea-bed terrain type were derived from GPS data. Identification photographs were matched so that the habitat choices could be established within breeding seasons. Across 72 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 69 publications
1
45
0
Order By: Relevance
“…Migrating mother-calf pairs of grey whales (Eschrictus robustus), right whales (Eubalaena spp.) and humpback whales (Megaptera novaeangliae) move close to shore in shallow waters while on their breeding grounds, compared with conspecific adults unaccompanied by a calf (Whitehead and Moore, 1982;Payne, 1986;Swartz, 1986;Pack et al, 2017). Specifically, on their breeding grounds, southern right whale (Eubalaena australis) mother-calf pairs primarily reside in very shallow water of 5-10 m depth close to shore, in close proximity to or in the surf zone (Payne, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Migrating mother-calf pairs of grey whales (Eschrictus robustus), right whales (Eubalaena spp.) and humpback whales (Megaptera novaeangliae) move close to shore in shallow waters while on their breeding grounds, compared with conspecific adults unaccompanied by a calf (Whitehead and Moore, 1982;Payne, 1986;Swartz, 1986;Pack et al, 2017). Specifically, on their breeding grounds, southern right whale (Eubalaena australis) mother-calf pairs primarily reside in very shallow water of 5-10 m depth close to shore, in close proximity to or in the surf zone (Payne, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have observed humpback whales in warm waters between 21°C and 28°C, including Silver Bank (West Indies), Antongil Bay (Madagascar), the Great Barrier Reef, and Hawai'i (Ersts & Rosenbaum, ; Johnston, Chapla, Williams, & Mattila, ; Rasmussen et al, ; Smith et al, ; Whitehead & Moore, ). A majority of humpbacks were observed in shallow waters less than 30 m in depth in Antongil Bay, between 15 and 60 m in the West Indies, 30–58 m in the Great Barrier Reef, and between 40 and 80 m in Hawai'i (Ersts & Rosenbaum, ; Pack et al, ; Smith et al, ; Whitehead & Moore, ). Depth may have an impact on different breeding behaviours, such as needing deeper waters for mating displays or shallower waters for young calves (Ersts & Rosenbaum, ).…”
Section: Discussionmentioning
confidence: 99%
“…Habitat models suggest a preference for nearshore shallow waters in accordance with other humpback whale breeding grounds around the world (Bortolotto, Danilewicz, Hammond, Thomas, & Zerbini, 2017;Cartwright et al, 2012;Lindsay et al, 2016;Martins et al, 2001;Oviedo & Solís, 2008;Smith et al, 2012;Trudelle et al, 2018 (Mercado III & Frazer, 1999), hence potentially constraining the spatial distribution of singing males. Rugged (Pack et al, 2017) and/or shallow habitats (Mercado & Frazer, 1999), such as that of the South Lagoon reef complexes, could be less suitable for acoustic communication, and therefore less attractive for singers and their audience. Based on these distributional preferences, the Merlet integral reserve (IUCN category Ia) was rarely used by humpback whales in the New Caledonia South Lagoon.…”
Section: Discussionmentioning
confidence: 99%